Poor prognosis, hypomethylation, and immune infiltrates are associated with downregulation of INMT in head and neck squamous cell carcinoma - Cui, Kun; Yao, Xi; Wei, Zhengbo; yang, Yujia; Liu, Xinli; Huang, Zhongheng; Huo, Huimin; Tang, Jinping; Xie, Ying (Frontiers in Genetics, 2022)
Background: Indiolethylamine-N-methyltransferase (INMT) is a methyltransferase responsible for transferring methyl groups from methyl donor SAM to its substrate. S-adenosyl-l-methionine (SAM), obtained from the methionine cycle, is a naturally occurring sulfonium compound that is vital to cellular metabolism. The expression of INMT is down-regulated in many tumorous tissues, and it may contribute to tumor invasion and metastasis. Nevertheless, the expression of INMT and its relationship to methylation and immune infiltrates in head and neck squamous cell carcinoma (HNSC) remains a mystery. Thus, we evaluated expression, clinicopathological features, prognosis, several critical pathways, DNA methylation, and immune cell infiltration for the first time. Methods: Analysis of the clinicopathological characteristics of INMT expression, several tumor-related bioinformatics databases were utilized. In addition, the role of INMT expression was analyzed for prognosis. Several INMT-related pathways were enriched on the LinkedOmics website. In addition, we have analyzed the methylation of INMT in HNSC in detail by using several methylation databases. Lastly, the relationship between INMT gene expression and immune infiltration was analyzed with ssGSEA, Timer, and TISIDB. Results: In HNSC, mRNA and protein levels were significantly lower than in normal tissues. The low expression of INMT was statistically associated with T stage, histological grade, gender, smoking history, and alcohol consumption. HNSC patients with low INMT expression have a poorer OS (overall survival) compared to those with high levels of expression. In addition, the multivariate analysis revealed INMT expression to be a remarkable independent predictor of prognosis in HNSC patients. An analysis of gene enrichment showed that several pathways were enriched in INMT, including the Ras signaling pathway, the cGMP-PKG signaling pathway, and others. Moreover, methylation patterns of INMT detected in a variety of methylation databases are closely associated with mRNA expression and prognosis. Finally, INMT was significantly correlated with immune infiltration levels. Conclusion: HNSC with low levels of INMT exhibits poor survival, hypomethylation, and immune infiltration. For HNSC, this study presented evidence that INMT is both a biomarker of poor prognosis and a target of immunotherapy.